Rancang Bangun Sistem Informasi Administrasi Dan Kearsipan Properti (Studi Kasus: PT. DSG SURABAYA) - Fendriawati, Erma Dwi; Tanuwijaya, Haryanto; Rahardianto, Panca (Jurnal JSIKA, 2012)
PT. DSG Surabaya is a company engaged in the sale of property, especially land and buildings. During this PT. DSG Surabaya experienced difficulties in the administration and archiving of documents in the form of sheets of paper, so the risk of being lost and often complicate the search. The absence of monitoring will be the completeness of documents, so that frequent delays in the completion of the land deed. Besides the lack of warning before the payment due date, so the buyers the installment payment is often not timely. To realize that, the company needs a system of administrative and archival properties are equipped warning system to be able to overcome the obstacles that occur with the purpose of assisting the task of the administration to improve service to the buyer. Also assist managers in making decisions related to increased sales poperti. The conclusion of the test results is an application that is built has to be applied by the company. Warning System can walk the walk in line with expectations. Keyword: Administration, Property, Warning System